DILEMMA CRIMINAL DISPARITY AND CONSIDERATIONS JUDGES IN COURT PRACTICE - Labaka, Albri Bri; Widowati, Yeni (Khairun Law Journal, 2025)
This study aims to examine the factors that affect different sentences or criminal disparities and the reasons underlying the judge's decision in adjudicating criminal cases during trial. The methodology of this study uses doctrinal legal research using legal and conceptual approaches. The results of the study show that criminal disparity has an underlying cause, which can be analyzed from theoretical, legal, and empirical perspectives. Legal theory argues that the autonomy and freedom granted to judges is based on the Constitution of the Republic of Indonesia of 1945 and Law No. 48 of 2009, which regulates the current judicial power. Then the deciden ratio theory, along with disagreement, equilibrium theory, intuition art theory, experience theory, and science theory, explains criminal disparity. Indonesian courts now use a punishment system that is exclusively based on trial exams. This leads to discrepancies in judicial decisions by judges, known as criminal disparita. At the very least, consider criteria related to exterior activities and subjective elements such as motives and objectives. Next, evaluate the impact of the action, the gravity of the violation, the approach used, the internal disposition (wrong), and relevance to the core of consideration. Judges cannot rely solely on procedural factors